Characterization of a Novel Monoclonal Antibody (27H2) Recognizing Human CD34 Class III Epitope - Hong, Kwon-Pyo; Kang, Sung-Hee; Lee, Kyoung-Mee; Ji, Gil-Yong; Yoon, Sang-Soon; Kim, Jong-Suk; Son, Bo-Ra; Lee, Dong-Geun; Lee, Ok-Jun; Song, Hyung-Geun (Immune network, 2010)
Monoclonal antibodies (mAbs) recognizing Class III epitope of CD34 are essential for flow cytometric diagnosis of leukemia. 27H2 mAb was developed from a mouse alternatively immunized with human acute leukemia cell lines, KG1 and Molm-1. Using flow cytometric analysis of various leukemic cell lines and peripheral blood, immunohistochemical study of frozen tonsil, we characterized 27H2 mAb. Antigen immunoprecipitated with 27H2 mAb immunobloted with anti-CD34 mAb. A case of bone marrow sample of acute lymphoblastic leukemia (ALL) patient was obtained at CBNU Hospital. For epitope identification enzyme treatment with neuraminidase and O-sialoglycoprotein endopeptidase (OSGE) and blocking assay with known classIII mAb (HPCA-2) were done. Only KG1 and Molm-1 revealed positive immunoreactivity. Immunohistochemical staining disclosed strong membranous immunoreactivity on high endothelial venules. Antigen immunoprecipitated by 27H2 mAb showed approximately 100 kDa sized band immunoblotted with anti-CD34 under non-reducing conditions. Epitope recognized by 27H2 mAb disclosed resistancy to both neuraminidase and OSGE treatment and completely blocked with known class III mAb preincubation. CD34 positive leukemic cells in BM of pre B cell ALL patient detected by FITC-conjugated 27H2 and HPCA-2 were identified with similar sensitivity. A novel murine mAb recognizing class III epitope of human CD34 with high affinity, which is useful for flow cytometric diagnosis of leukemia, was developed.